2009
DOI: 10.1016/j.jjcc.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of dyslipidemia for coronary plaque vulnerability in acute coronary syndrome without metabolic syndrome

Abstract: In ACS patients without the metabolic syndrome, high LDL cholesterol levels and carotid artery remodeling are important indicators for assessing the efficacy of aggressive treatments for secondary prevention of ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…In contrast with our study, previous epidemiological studies have shown that long-term morbidity and mortality in coronary artery disease, manifest over years, is directly related to circulating levels of atherogenic lipoproteins, in particular LDL cholesterol [28]. Also, Kato et al showed that high LDL cholesterol level is an independent predictor of vulnerability to coronary plaque formation in ACS patients without MetS [29]. However, the Tromsø study provided evidence for antiatherogenic effects of HDL, relating to both inhibition of plaque growth and enhanced plaque stability [30].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our study, previous epidemiological studies have shown that long-term morbidity and mortality in coronary artery disease, manifest over years, is directly related to circulating levels of atherogenic lipoproteins, in particular LDL cholesterol [28]. Also, Kato et al showed that high LDL cholesterol level is an independent predictor of vulnerability to coronary plaque formation in ACS patients without MetS [29]. However, the Tromsø study provided evidence for antiatherogenic effects of HDL, relating to both inhibition of plaque growth and enhanced plaque stability [30].…”
Section: Discussioncontrasting
confidence: 99%
“…Obesity and metabolic syndrome are mainly caused by the lack of regular exercise and excessive intake of calories on a daily basis. Obesity has been proven to be an important risk factor for cardiovascular disease and for all-cause mortality [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement was observed in each of these markers after the administration of fluvastatin. We selected these markers because (1) recently, a markedly advanced molecular biological method was used to analyze the pathogenic mechanism of arteriosclerosis or atherosclerosis, and the above markers were found to be associated with vascular remodeling and the subsequent development of arteriosclerosis or atherosclerosis, and (2) these markers have been widely used to assess the clinical conditions or treatment of atherosclerosis in adult patients with obesity, hypertension, hyperlipidemia, or diabetes mellitus [26][27][28][29][30][31][32]37]. It has been suggested that KD eventually leads the development of post-inflammatory arteriosclerosis [2,3].…”
Section: Discussionmentioning
confidence: 99%